Bioethanol Production from Wastewater of Brown Sugar Home Industry in Kediri via Enzymatic Hydrolysis and Fermentation - Soeprijanto Soeprijanto; Afan Hamzah; Nabila Fara Anindya; Putri Selly Mudyawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Bioethanol is ethanol whose main ingredients are from plants and generally use a pharmaceutical process. Therefore, Indonesia still needs a more effective source of bioethanol as fuel. Bioethanol production from vegetable waste is a realistic solution, one example is waste from the brown sugar home industry. The purpose of this research is to innovate the production of bioethanol by utilizing sap sugarcane waste in a brown sugar industry home using the Enzyme Hydrolysis and Fermentation Method. The process of making bioethanol is the raw material preparation stage, the hydrolysis stage, and the fermentation stage. The first stage, the preparation of raw materials is done by filtering the molasses waste and then dissolving it with distilled water in 2000 mL Erlenmeyer. the second stage, the hydrolysis stage, is to hydrolyze the molasses solution according to the predetermined ratio variables, by going through two stages in the hydrolysis stage, namely liquefaction and saccharification. In the liquefaction process, -amylase is added at a temperature of 90oC and heated on a hot plate stirrer for 2 hours. Then the saccharification stage was carried out by adding the enzyme gluco-amylase at a temperature of 65oC for 4 hours. The third stage, the fermentation stage, was carried out with variations of bread and yeast tape with the additional variables of 5%, 10%, and 15% nutrient (2% urea and 3%). Fermentation will be carried out for 3 days. The results showed that the maximum sugar content was achieved by using a concentration ratio of sugarcane juice: water = 1:0 with an enzyme hydrolysis process of 196.08 g/L. The maximum bioethanol content after fermentation was 18.6% and reducing sugar of 10.98 g/L was achieved by using 10% baker's yeast at a concentration of sugar cane juice: water ratio = 1:1. The maximum bioethanol content after the fermentation process was 12.96% and the reducing sugar was 27.78 g/L was achieved using 10% tape yeast at a concentration ratio of sugarcane juice: water = 1:1.